Comparison of alfentanil and lignocaine in blunting the pressor response during endotracheal intubation - Moumakoe, Stella Josephine (University of Limpopo (Medunsa Campus), 2007)
Comparison of Alfentanil and Lignocaine in blunting the pressor response during endotracheal intubation. Laryngoscopy and tracheal intubation produce marked increases in heart rate and blood pressure, which is potentially dangerous in certain patients. Various pharmacological agents have been used before laryngoscopy and tracheal intubation in an attempt to attenuate the adrenergic response, but with varying degree of success. OBJECTIVE To compare the efficacy of lignocaine to alfentanil in blunting the pressor response to endotracheal intubation. DESIGN An open label comparative study. POPULATION Seventy eight ASA I and II adult patients between the ages of 18 and 65 years booked for elective surgery which requires endotracheal intubation. SETTING Dr George Mukhari Hospital, a tertiary level training hospital in Gauteng, South Africa. 2 METHOD After obtaining ethical clearance the study was conducted on 78 ASA class I & II patients. The patients were randomly allocated to three groups according to their treatment regime. All patients were premedicated with diazepam 10mg 2 hours pre operatively. Anaesthesia was induced with Thiopentone 5mg/kg followed by Vecuronium 0,1mg/kg and maintained with Isoflurane in nitrous oxide and oxygen mixture. Group A patients received lignocaine 1.5mg/kg iv 3 minutes before intubation. Group B – alfentanil 15ug/kg iv 1 minute before intubation and group C patients did not receive any treatment before intubation. Heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure were recorded at the following intervals: pre- induction, pre- intubation 1, 2 and 3 minutes post intubation. STATISTICS Statistical analysis was done by Chi Square test followed by the normal approximation of the binomial distribution. Increase in blood pressure and heart rate in the three treatment groups were compared by analysis of variance, followed by pairwise comparisons. A p- value <_ 0,05 was considered significant. 3 MAIN RESULT The three treatment groups did not differ in relation of Gender ratio, Mean weight and Mean age. ALFENTANIL GROUP There was a non significant increase in heart rate 1 minute post intubation (P= 0,7625), and there was no increase 2 and 3 minutes post intubation. A decrease in SBP, DBP and MAP was observed at 1, 2 and 3 minutes post intubation. LIGNOCAINE GROUP There was an increase in all parameters 1 minute post intubation which was comparable to the control group. A decrease in all parameters which differed from that of the control group except for heart rate, was observed at 2 and 3 minutes post intubation. CONTROL GROUP There was an increase in all parameters 1 minute post intubation. A decrease in all parameters 2 and 3 minutes post intubation remained above the baseline. CONCLUSION Alfentanil is superior to lignocaine in blunting the pressor response to endotracheal intubation.
Theses (M Med.(Anaesthesiology))--University of Limpopo, 2007.
Keywords: Alfentanil; Lignocaine; Endotracheal intubation